Software architecture for web-based project management system - Esteca, Antonio Marcos Neves [UNESP]; De Souza, Rogéria Cristiane Gratão [UNESP]; Santos, Adriana Barbosa [UNESP] (My University, 2010)
This article presents software architecture for a web-based system to aid project managing, conceptually founded on guidelines of the Project Management Body of Knowledge (PMBoK) and on ISO/IEC 9126, as well as on the result of an empiric study done in Brazil. Based on these guidelines, this study focused on two different points of view about project management: the view of those who develop software systems to aid management and the view of those who use these systems. The designed software architecture is capable of guiding an incremental development of a quality system that will satisfy today's marketing necessities, principally those of small and medium size enterprises.
Keywords: Body of knowledge; Incremental development; ISO/IEC 9126; Project management system; Quality systems; Small and medium-size enterprise; Software systems; Web-based system; Diamonds; Multimedia systems; Project management; World Wide Web; Software architecture